Ovulation induced by mucosa vaginal absorption of buserelin and triptorelin in rabbit - Viudes-De-Castro, María P.; Lavara, R.; Marco-Jiménez, Francisco; Cortell, Carmela; Vicente, José Salvador (2017)
The aim of this study was to evaluate the supplementation of semen extender with two synthetic GnRH analogues (buserelin and triptorelin) to induce ovulation in rabbit does submitted to artificial insemination. In a first experiment, 255 receptive multiparous does were inseminated with 0.5 mL of Tris-citrate-glucose extender supplemented or riot with two GnRH synthetic analogues. Experimental groups were: NC (not supplemented extender), PC (not supplemented extender and does treated with 1 mu g of buserelin i.m.), 132 (2 mu g per female buserelin supplemented extender), 135 (5 mu g per female buserelin supplemented extender), T2 (2 mu g per female triptorelin supplemented extender) and T5 (5 mu g per female triptorelin supplemented extender). Thirteen does of NC females ovulated, reaching an ovulation rate similar to the other groups. Ovulation rate was similar in all groups (11.4-12.5). The efficiency of ovulation induction was very low (32.5%) in NC group and showed the higher results in PC females (97.8%). Only 135 females reached similar ovulation induction response than PC group. In a second experiment, 702 receptive does were inseminated to compare fertility and prolificacy parameters from the conventional insemination technique (control group, females treated with 1 mu g per female of buserelin intramuscularly) versus a supplementation with buserelin or triptorelin (5 mu g per female) in semen extender (135 and T5 groups, respectively). Fertility and prolificacy parameters were similar among the groups (77.8% fertility rate, 73.9% kindling rate, 9.4 live born and 9.9 total born). This study demonstrate the possibility of ovulation induction in rabbits by adding two GnRH synthetic analogues in the seminal doses and open up new prospects for changing rabbit insemination procedures. (C) 2007 Elsevier Inc. All rights reserved.